-9x+y=12 2x+4y=-28

1 answer

To solve this system of equations, we can use the method of substitution or elimination.

First, we will solve the first equation for y:
-9x + y = 12
y = 9x + 12

Next, we will substitute this expression for y into the second equation:
2x + 4(9x + 12) = -28
2x + 36x + 48 = -28
38x + 48 = -28
38x = -76
x = -2

Now that we have found the value of x, we can substitute it back into one of the original equations to solve for y. Let's use the first equation:
-9(-2) + y = 12
18 + y = 12
y = -6

Therefore, the solution to the system of equations is x = -2, y = -6.